Pengukuran Overall Equipment Effectiveness (Oee) Pada Mesin Spinning Di PT. Kurabo Manunggal Textile - Nur Fadilah Fatma; Henri Ponda; Muhammad Ghifari Nurwahid (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
Machines and equipment are one of the main strengths in supporting the continuity of the production process. To produce high-quality products, machines must be kept in optimal condition; therefore, appropriate systems and methods must be implemented. This thesis applies the Overall Equipment Effectiveness (OEE) method to determine the OEE value of the spinning machine and identify the dominant factors affecting productivity in the spinning machine. Overall Equipment Effectiveness is a comprehensive measurement tool involving three main components: availability, performance, and quality. Meanwhile, the Six Big Losses can be used to identify the causes of problems in the spinning machine. Based on the OEE calculation, the average result obtained is 64.62%. Additionally, the Six Big Losses calculation reveals the factors affecting the effectiveness of the spinning machine, including idle and minor stoppages at 31.89%, reduce speed losses at 30.32%, equipment failure losses at 5.60%, setup losses at 2.34%, defect losses at 1.78%, and reduce yield losses at 0.06%.Â Keyword : Maintenance, spinning machine, Overall Equipment Effectiveness, Six Big Losse